Digital technologies as didactic tools mediating educational practices - João Victor da Silva; Dirce Aparecida Foletto de Moraes (Universidade Federal do Oeste da Bahia, 2021)
The relation ships between contemporary subjects and digital technologies increasingly focus the need for an understanding of their practice also in the school environment. In this sense, this study seeks to understand if the digital technologies used in educational practices and the ways in which they are used become didactic tools that mediate the students' learning. This is a qualitative, exploratory-exploratory study. To this end, a bibliographic and field research was carried out, in the year 2020, with a group of teachers from the Londrina municipal school system who have already used some digital technology in their educational practices. The results indicate that mediation occurred from the intentional use of digital technologies, generating positive aspects for the learning process. It was also possible to verify that the ways of using digital technologies showed evidence of student autonomy, interaction among subjects, new understandings about concepts, and other ways of constructing knowledge.